Are orthopaedic providers willing to work overtime to address COVID-19-related patient backlogs and financial deficits? - Montgomery, Zachary A. (Bone Jt Open, 2021)
AIMS: COVID-19-related patient care delays have resulted in an unprecedented patient care backlog in the field of orthopaedics. The objective of this study is to examine orthopaedic provider preferences regarding the patient care backlog and financial recovery initiatives in response to the COVID-19 pandemic. METHODS: An orthopaedic research consortium at a multi-hospital tertiary care academic medical system developed a three-part survey examining provider perspectives on strategies to expand orthopaedic patient care and financial recovery. Section 1 asked for preferences regarding extending clinic hours, section 2 assessed surgeon opinions on expanding surgical opportunities, and section 3 questioned preferred strategies for departmental financial recovery. The survey was sent to the institution’s surgical and nonoperative orthopaedic providers. RESULTS: In all, 73 of 75 operative (n = 55) and nonoperative (n = 18) providers responded to the survey. A total of 92% of orthopaedic providers (n = 67) were willing to extend clinic hours. Most providers preferred extending clinic schedule until 6pm on weekdays. When asked about extending surgical block hours, 96% of the surgeons (n = 53) were willing to extend operating room (OR) block times. Most surgeons preferred block times to be extended until 7pm (63.6%, n = 35). A majority of surgeons (53%, n = 29) believe that over 50% of their surgical cases could be performed at an ambulatory surgery centre (ASC). Of the strategies to address departmental financial deficits, 85% of providers (n = 72) were willing to work extra hours without a pay cut. CONCLUSION: Most orthopaedic providers are willing to help with patient care backlogs and revenue recovery by working extended hours instead of having their pay reduced. These findings provide insights that can be incorporated into COVID-19 recovery strategies. Level of Evidence: III Cite this article: Bone Jt Open 2021;2(7):562–568.